Poverty in rural India: ethnicity and caste - Ira N. Gang; Kunal Sen; Myeong-Su Yun (Rutgers University, Department of Economics, 2006)
This paper analyzes the determinants of rural poverty in India, contrasting the situation of scheduled caste (SC) and scheduled tribe (ST) households with the non-scheduled population. The incidence of poverty in SC and ST households is much higher than among non-scheduled households. By combining regression estimates for the ratio of per capita expenditure to the poverty line and an Oaxaca-type decomposition analysis, we study how these differences in the incidence of poverty arise. We find that for SC households, differences in characteristics explain the gaps in poverty incidence more than differences in transformed regression coefficients. In contrast, for ST households, the transformed regression coefficients play the more important role.
Keywords: I32; O12; J15; 330; Poverty; caste; ethnicity; decomposition